2021
DOI: 10.3390/nu14010122
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Factors and Constipation in Adults Living in Luxembourg and Taking Part in the ORISCAV-LUX 2 Survey

Abstract: Constipation, a disorder of bowel movements, is among the most frequent gastrointestinal complaints in Western countries. Dietary constituents such as inadequate fiber intake have been related to constipation, but discrepancies exist in the findings regarding dietary factors. This study investigated the association between dietary patterns and bowel movements in adults living in Luxembourg. Data from 1431 participants from ORISCAV-LUX 2 (a cross-sectional survey) who completed a 174-item food frequency questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Numerous epidemiological investigations have shown an association between diet and constipation, focusing mainly on the effects of individual nutrients or foods and food groups [ 28 , 29 ]. According to our survey, 98% of university students accounted for high DDS, indicating that the majority of university students consumed a wide variety of foods and had a diverse diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous epidemiological investigations have shown an association between diet and constipation, focusing mainly on the effects of individual nutrients or foods and food groups [ 28 , 29 ]. According to our survey, 98% of university students accounted for high DDS, indicating that the majority of university students consumed a wide variety of foods and had a diverse diet.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that individuals who prefer high-fat foods, junk snacks, fried foods, or coffee, alcohol, and spices had a higher prevalence of gastrointestinal symptoms [ 33 , 34 ]. Rollet et al showed a positive correlation between the occurrence of constipation and sugary products and higher energy intake [ 29 ]. When high-fat, high-energy foods, as well as sugary foods and alcohol, are consumed at high levels, a high prevalence of FC is more likely to occur, which is in line with our study results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Notably, processed foods (rich in AGEs) are associated with constipation. 22 Consistently, children with autism spectrum disorder who consumed ultra-processed foods showed symptoms of constipation. 23 Thus, dietary AGEs lead to increased colonic length, which may be involved in the pathology of colonic volvulus.…”
Section: Effects Of Gos On the Body Weight And Colon Length In Mice W...mentioning
confidence: 97%